2014
DOI: 10.1080/17470218.2014.910240
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in forced-choice recognition memory: Partitioning contributions of recollection and familiarity

Abstract: In forced-choice recognition memory, two different testing formats are possible under conditions of high target-foil similarity: each target can be presented alongside foils similar to itself (forced-choice corresponding; FCC), or alongside foils similar to other targets (forced-choice non-corresponding; FCNC).Recent behavioural and neuropsychological studies suggest that FCC performance can be supported by familiarity whereas FCNC performance is supported primarily by recollection. In this paper, we corrobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 64 publications
4
27
0
Order By: Relevance
“…In both age groups, performance was best on the A-X format, followed by the A-A’ format, followed by the A-B’ format. These findings support previous studies that have reported better performance on the A-A’ test format than the A-B’ test format (Tulving, 1981; Hintzman, 1988; Jeneson et al, 2010; Migo et al, 2014) while also raising the question of why performance is worse on the the A-B’ test format than the A-A’ test format. One possibility is that the presence of the A-X test format was affecting performance on the A-B’ test format.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In both age groups, performance was best on the A-X format, followed by the A-A’ format, followed by the A-B’ format. These findings support previous studies that have reported better performance on the A-A’ test format than the A-B’ test format (Tulving, 1981; Hintzman, 1988; Jeneson et al, 2010; Migo et al, 2014) while also raising the question of why performance is worse on the the A-B’ test format than the A-A’ test format. One possibility is that the presence of the A-X test format was affecting performance on the A-B’ test format.…”
Section: Discussionsupporting
confidence: 90%
“…We reanalyzed published data from our lab (Experiment 4 in Stark et al, 2015) to examine whether there were differences in performance between the forced-choice test format and the old/new test format with confidence ratings. Specifically, if the forced-choice test format allowed participants to rely on familiarity to a greater extent than the old/new test format (Holdstock et al, 2002; Norman & O’Reilly, 2003; Migo et al, 2009, 2014), then we should observe significantly better performance on the forced choice test format than A z from the old/new test format. Conversely, if the two test formats rely on similar cognitive processes, then we should not observe a difference between the two test formats.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…was impaired for the ONR task, however her forced-choice task performance was not significantly different from normal controls (even when tested using similar lures, similar to the state comparison from Brady et al (2008)). Additionally, it has been shown that the contributions of familiarity and recollection memory sources can differ depending on the type of items that are presented in forced-choice memory tests (Migo et al 2014). These results suggest that regions outside the hippocampus are capable of supporting high performance on forced-choice tasks.…”
mentioning
confidence: 99%